2022
DOI: 10.1186/s12872-022-02738-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of functional variant of aldehyde dehydrogenase 2 with acute myocardial infarction of Chinese patients

Abstract: Background The variant of ALDH2 was thought to be associated with Acute Myocardial Infarction (AMI) due to the consumption of alcohol. This study focused on how ALDH2 variant acts as an independent risk factor for AMI, regardless of alcohol consumption. Methods and results We used the case–control INTERHEART-China study which took place at 25 centres in 17 cities in mainland China. Cases were patients with AMI and matched by age, sex, and site to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Previous research has shown that ALDH2 malfunction is linked to many human disorders, for instance, diabetes, cardiovascular disease, Fanconi anemia, pain, osteoporosis, and cancer. [18][19][20][21][22][23] ALDH2 research has gotten a lot of attention in the biological, medical, and chemical communities because around 30% to 40% of Asians are genetically deficient in this enzyme and are exposed to high levels of the catalytically active form of acetaldehyde. 23,24 Alcohol consumption and smoking are definite risk factors for HNSC in the oral cavity, pharynx, and larynx.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that ALDH2 malfunction is linked to many human disorders, for instance, diabetes, cardiovascular disease, Fanconi anemia, pain, osteoporosis, and cancer. [18][19][20][21][22][23] ALDH2 research has gotten a lot of attention in the biological, medical, and chemical communities because around 30% to 40% of Asians are genetically deficient in this enzyme and are exposed to high levels of the catalytically active form of acetaldehyde. 23,24 Alcohol consumption and smoking are definite risk factors for HNSC in the oral cavity, pharynx, and larynx.…”
Section: Discussionmentioning
confidence: 99%